PENGARUH EKSTRAK ETANOL DAUN KEMANGI (Ocimum bacilicum L.) TERHADAP KADAR β2 MIKROGLOBULIN, ASAM URAT DAN GAMBARAN HISTOLOGI GINJAL PADA TIKUS PUTIH GALUR WISTAR (Rattus novergicus strain Wistar) YANG DIINDUKSI MONOSODIUM GLUTAMAT - Paramita Septianawati; Hernayanti Hernayanti; Gratiana Ekaningsih W (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
AbstractBasil leaves (Ocimum basilicum) is one of the traditional medicinal plants that is used as medicine.This study aims to determine the effect of giving basil leaves on levels of Beta 2 microglobulin, uric acid and kidney histology in white wistar-induced rats in MSG and determine the effective dose of basil leaves in an effort to improve kidney function.This study used 25 male Wistar strain rats with body weight 200-230 g. The test animal group was divided into five groups based on the stage of treatment. The first treatment group was a control group consisting of five mice that were not given basil leaf extract or MSG, the second treatment group was the group that was only given MSG without being given basil leaf extract, the third treatment group was the group given MSG followed by basil leaf extract dose 87, 5 mg / kgBB, the fourth treatment group was the group that was given MSG followed by the administration of basil leaf extract with a dose of 175 mg / kgBW, and the fifth treatment group was the group that was given MSG followed by the administration of basil leaf extract at a dose of 350 mg / kgBB. At the end of the treatment, rats were drawn for blood analysis of B2M levels and uric acid levels and kidney tissue uptake, as well as analyzing kidney tissue histology.The results showed that there were differences between Beta 2 microglobulin, uric acid and kidney histopathology of rats receiving basil leaf extract compared with MSG group without basil leaf extract. This study concludes that consuming basil leaf extract can reduce levels of B2M and uric acid and improve kidney histology induced by MSG.